2013
DOI: 10.1186/1475-925x-12-87
|View full text |Cite
|
Sign up to set email alerts
|

Tissue engineering of heart valves: PEGylation of decellularized porcine aortic valve as a scaffold for in vitro recellularization

Abstract: BackgroundPoly (ethylene glycol) (PEG) has attracted broad interest for tissue engineering applications. The aim of this study was to synthesize 4-arm -PEG-20kDa with the terminal group of diacrylate (4-arm-PEG-DA) and evaluate its dual functionality for decellularized porcine aortic valve (DAV) based on its mechanical and biological properties.Methods4-arm-PEG-DA was synthesized by graft copolymerization of linear PEG 20,000 monomers, and characterized by IR1H NMR and 13C NMR; PEGylation of DAV was achieved b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…17 Polyethylene glycol (PEG) is a long chain polymer that is widely used in tissue engineering, medicine, food, owing to its high degree of hydrophilicity, water solubility, good biocompatibility and lack of toxicity. [23][24][25][26][27] The synthetic hydrophilic polymer PEG and its derivatives are the most widely used antifouling and anti-bacterial materials. AMPs can be covalently immobilised using PEG that bears functional groups suitable for covalent peptide immobilisation.…”
Section: Introductionmentioning
confidence: 99%
“…17 Polyethylene glycol (PEG) is a long chain polymer that is widely used in tissue engineering, medicine, food, owing to its high degree of hydrophilicity, water solubility, good biocompatibility and lack of toxicity. [23][24][25][26][27] The synthetic hydrophilic polymer PEG and its derivatives are the most widely used antifouling and anti-bacterial materials. AMPs can be covalently immobilised using PEG that bears functional groups suitable for covalent peptide immobilisation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, complete repopulation of the scaffold and its functional restoration have as of yet not been successful. There are many more difficulties in the recellularization process, and often incorporation of certain growth factors or bioactive molecules are needed to enhance the function of the created tissue . But also technical challenges are a reason for the unsuccessful recellularization of kidney scaffolds.…”
Section: Current and Novel Applications Of Membrane Technology In Kidmentioning
confidence: 99%
“…Additionally, the incorporation of certain growth factors or bioactive molecules into the decellularized scaffolds could also result in enhanced functionality of the recellularized tissue/organ constructs. For instance, Zhou et al () reported the potential of decellularized porcine aortic valve functionalized with Gly–Arg–Gly–Asp–Ser–Pro–Cys (GRGDSPC) peptides and vascular endothelial growth factor‐165 (VEGF 165 ) for enhanced cellular immobilization and proliferation of human umbilical vein endothelial cells (HUVECs). Various bioactive molecules that can be incorporated into the decellularized scaffolds to enhance the functionality are shown in Table .…”
Section: Recellularizationmentioning
confidence: 99%